ANALISIS KEBUTUHAN PENGEMBANGAN LEMBAR KERJA DIGITAL GEOMETRI ANALITIK DATAR: Need Analysis of Developing Analytical Geometry Digital Worksheet - Nasir, Rahma; Alfisyahra, Alfisyahra; Karniman, Tegoeh S. (Universitas Tadulako, 2023)
Digital visualization of mathematical concepts makes it difficult for students to learn and this results in a lack of understanding and participation of students. This study aims to analyze the needs of developing worksheets in flat analytical geometry courses for students of the mathematics education study program. The method used is qualitative research. On the worksheet there is an exploration of three-dimensional shapes on flat analytical geometry, practice questions created using the features available on GeoGebra. Data is collected through written tests and interviews with course lecturer students. The data is then analyzed descriptively quantitatively to determine student knowledge related to the material contained in GAD. From the results of the analysis, it was obtained that students had low scores on knowledge In addition, the results of interviews with lecturers who teach GAD courses also showed difficulty in conveying an understanding of 3D images. For this reason, digital worksheets that can help students to visualize the two- and three-dimensional builds in the GAD course are very necessary.